2013
DOI: 10.1038/nphys2833
|View full text |Cite
|
Sign up to set email alerts
|

Switching of magnetic domains reveals spatially inhomogeneous superconductivity

Abstract: The interplay of magnetic and charge fluctuations can lead to quantum phases with exceptional electronic properties. A case in point is magnetically-driven superconductivity 1,2 , where magnetic correlations fundamentally affect the underlying symmetry and generate new physical properties. The superconducting wave-function in most known magnetic superconductors does not break translational symmetry. However, it has been predicted that modulated triplet p-wave superconductivity occurs in singlet d -wave superco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(108 citation statements)
references
References 30 publications
6
101
0
1
Order By: Relevance
“…Subsequent NMR results (B.-L. Young et al [237]; Koutroulakis et al [238]) revealed evidence for a local moment in this region of the phase diagram, rather than the long wavelength spin density modulation expected for the FFLO phase. Using sensitive high field neutron diffraction on a 155 mg single crystal of CeCoIn5, Gerber et al [239] concluded that modulated triplet p-wave superconductivity occurs in the Q-phase due to the interaction of the host's d-wave superconductivity with the spindensity-wave (SDW) order discovered by NMR.…”
Section: Cecoin5mentioning
confidence: 99%
“…Subsequent NMR results (B.-L. Young et al [237]; Koutroulakis et al [238]) revealed evidence for a local moment in this region of the phase diagram, rather than the long wavelength spin density modulation expected for the FFLO phase. Using sensitive high field neutron diffraction on a 155 mg single crystal of CeCoIn5, Gerber et al [239] concluded that modulated triplet p-wave superconductivity occurs in the Q-phase due to the interaction of the host's d-wave superconductivity with the spindensity-wave (SDW) order discovered by NMR.…”
Section: Cecoin5mentioning
confidence: 99%
“…This last goal is particularly relevant for several materials. In heavy-fermion superconductor CeCoIn 5 , can an FFLO phase be the origin of coexistence [11][12][13] of antiferromagnetism (AFM) and superconductivity? On the other hand, is recently observed 14 enhancement of relaxation rate T −1 1 in organic superconductor κ-(BEDT-TTF) 2 Cu(NCS) 2 , indeed explained by Andreev bound states at FFLO domain walls?…”
Section: For Example In Triplet Superfluidmentioning
confidence: 99%
“…(28) and then, with Eq. (29), we find Calculation of Ω (4) In this case, after performing the ξ n (p) integral, the expression of…”
Section: Calculation Of ω (2)mentioning
confidence: 99%
“…(3). Next, the details of the derivation of the GL quadratic term Ω (2) and the quartic one Ω (4) are explained. The treatment to derive Ω (2) and Ω (4) given below closely follows that in the previous work [10].…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation